Socialization of Strengthening Lecturers' Motivation and Mentality in Implementing the Tri Dharma of Higher Education: Pengabdian - Rabith Madah Khulaili Harsya; Atjih Sukaesih Syahid; Usman Tahir; Alisyah Pitri; Nicodemus Rahanra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The author conducted this outreach to fellow writers to improve Mental Health and Motivation among fellow colleagues. The fellow writers consisted of fifteen lecturers at several universities, namely UIN Siber Syekh Nurjati Cirebon, Sultan Syarif Kasim State Islamic University Riau, Jayapura University of Science and Technology, Al-Mujaddid Sabak Islamic Institute, Satya Iyata Mandala University. The author hopes that lecturers who are currently carrying out their obligations under the Tri Dharma of Higher Education will remain motivated and mentally strong so that the Tri Dharma of higher education can be completed well, be beneficial, and can advance civilization. The success of fellow authors is also the success of the author personally.